Comparative Study of One Way and Two Way Communication Da'wah in the Religious Development of Mosque Youth - Juwita, Juwita; Qadaruddin, Muhammad; Sulvinajayanti, Sulvinajayanti (Institut Agama Islam Negeri Parepare, 2022)
This research uses a qualitative descriptive approach method. The techniques used in the form of data collection techniques are observation, interview, and documentation. Research results show that the problem of one way and two way communication for a Da'i will experience problems when delivering da'wah both one way and two way communication such as semantic barriers, psychological barriers, and socio-anthropological barriers. In the comparison of effectiveness between one way dakwah and two way dakwah both are good. It's just that the two-way preaching is more effective because it has been proven through the activity that teenagers have started to be confident when expressing their opinions when the discussion is going on